The Bird as a Sacrificial Hero in Oscar Wilde’s “The Nightingale and the Rose” and “The Happy Prince” (مجلة ديالى للبحوث الانسانية, 2022)
Heroism and sacrifice are not new concepts; they can be traced back to the early days of human life. These concepts developed throughout history as a result of the development of human thought. In literature, the idea of heroism appears on a large scale. It has been dealt with by different writers in different periods. As far as terminology is concerned, the terms of heroism and sacrifice are interchangeable. The hero must be a sacrificer and the one who sacrifices himself must be a hero, for this reason these two terms (hero and sacrificer) cannot be separated. Thus, both of them go hand in hand in so many works of literature. Heroism and sacrifice are not confined to human beings only. Some writers present their heroes as gods as in mythology, and some of them present animals as in fables.